New Insight for the Diagnosis of Gastrointestinal Acute Graft-versus-Host Disease - Florent Malard; Mohamad Mohty (Mediators of Inflammation)
Allogeneic stem cell transplantation (allo-SCT) is a curative therapy for different life-threatening malignant and nonmalignant hematologic disorders. Graft-versus-host disease (GVHD) remains a major source of morbidity and mortality following allo-SCT, which limits the use of this treatment in a broader spectrum of patients. Early diagnostic of GVHD is essential to initiate treatment as soon as possible. Unfortunately, the diagnosis of GVHD may be difficult to establish, because of the nonspecific nature of the associated symptoms and of the numerous differential diagnosis. This is particularly true regarding gastrointestinal (GI) acute GVHD. In the recent years many progress has been made in medical imaging test and endoscopic techniques. The interest of these different techniques in the diagnosis of GI acute GVHD has been evaluated in several studies. With this background we review the contributions, limitations, and future prospect of these techniques in the diagnosis of GI acute GVHD.